Analysis of spatial and temporal changes of the zooplankton fauna in the Ráckeve-Soroksár Danube arm - Mészáros, Gergely; Vadadi-Fülöp, Csaba; Udvari, Zsolt (TÁJÖKOLÓGIAI LAPOK, 2007)
The section of the Ráckeve-Soroksár Danube arm (RSD) can be divided based on the Cladocera and Copepoda fauna well. Strong dividing lines, however, cannot be drawn only based on hydromorphological aspects, just as considering the above mentioned two faunas. For example, in the middle section of the arm there are no exclusively characteristic species. This fact is obvious as the river stretch here offers the most various habitats. The upper section can be separated well from the middle one and, the lower section is sharply separated from the other two sections. Though numerous sources of pollution have ceased, the number of species shows a decreasing tendency. A possible reason for this is eutrophication. Statistical analyses also reinforce the existence of spatial and temporal changes.